Grandmaster of demonic cultivation, the comic = Mo dao zu shi. 3 - Moxiangtongxiu (Seven Seas Entertainment, 2023)
Wei Wuxian's studies come to an abrupt end when he picks a fight with a young master of the Jin Clan. A lifetime later, he wakes from his dream of days gone by to find he's still unraveling the mystery of the ghost arm. Following their latest lead, Wei Wuxian and Lan Wangji arrive in Qinghe, where they must contend with strange tombs interring sabers, terryfing man-eating walls, and bizarre sewn-up corpses. But that's not even the worst of it. Wei Wuxian's true identity has been revealed! How will he settle his past scores.